2019
DOI: 10.1111/dme.14183
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of calcaneal quantitative ultrasound and bone densitometry parameters as fracture risk predictors in type 2 diabetes mellitus

Abstract: Aim To investigate the utility of calcaneal quantitative ultrasound compared with bone densitometry (DXA) in predicting incident low-trauma fracture in type 2 diabetes. Methods This retrospective cohort study included a subset of participants in the Dubbo Osteoporosis Epidemiology Study who had concurrent calcaneal quantitative ultrasound and DXA measurement, comprising 809 people without type 2 diabetes and 96 with type 2 diabetes. Fracture data had been collected prospectively. Cox proportional hazard models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(40 citation statements)
references
References 28 publications
0
39
0
Order By: Relevance
“…We have previously proposed that QUS may have utility in bone health screening [ 13 ]; however, this data now suggests one would need to simultaneously screen for peripheral neuropathy. Peripheral measures of bone health are less likely to be representative of general bone health when peripheral neuropathy is present.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously proposed that QUS may have utility in bone health screening [ 13 ]; however, this data now suggests one would need to simultaneously screen for peripheral neuropathy. Peripheral measures of bone health are less likely to be representative of general bone health when peripheral neuropathy is present.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, central DXA may be more relevant. While we have previously shown that QUS is predictive of any low trauma fracture in T2DM [ 13 ], specific relevance to foot fracture and Charcot foot prediction would require further evaluation. Of interest, if QUS could be used to identify those at greatest risk of Charcot foot prior to its onset, there may be opportunity for preventative action.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 3 NRS used prospective cohort designs over a long-term duration of follow-up; that is, 20 years 18 5 years, 19 and over 20 years, 20 respectively. All 3 studies used both a portable bone imaging device and DXA to measure bone properties in each study participant and compare clinical utility across follow-up.…”
Section: Methodsmentioning
confidence: 99%
“…Other more complex QUS parameters include stiffness index, amplitude-dependent speed of sound, and bone transmission time. Although QUS parameters have shown correlations with aBMD [44,45] and bone microstructure [46], associations with risk of fracture [47], and even comparable predictive capabilities as femoral neck aBMD for low trauma incident fracture in T2D [48], the clinical utility of QUS is still limited as a prescreening tool mainly due to standardization issues between different manufacturers.…”
Section: Quantitative Ultrasoundmentioning
confidence: 99%